PENYULUHAN PENGARUH MAKANAN INSTAN TERHADAP POLA MAKAN DAN KESEHATAN REMAJA DI DESA MANUNGGAL - Yuana Delvika; Kamil Mustafa (Universitas Muhammadiyah Sumatera Utara, 2017)
Busyness in various activities such as school and work often make teenagers number two basic needs, such as food. More business entities increasingly competing to produce instant food. Teenage thinking patterns change as well.